PENGARUH PARTISIPASI TOKOH AGAMA DAN PERANAN PEMERINTAH DESA TERHADAP PEMBERDAYAAN EKONOMI MASYARAKAT MUSLIM DI DESA JANGKURANG KECAMATAN LELES KABUPATEN GARUT - Jalaluddin Jalaluddin (Jurnal Maps (Manajemen Perbankan Syariah), 2019)
Community Economic Empowerment is the obligation of all components of the nation including the participation of Religious Scholars and the role of the Government Apparatus (Regional Government) concerning formulation, implementation, monitoring, and evaluation by prioritizing the principles of democracy involving the role of equal distribution, justice prosperity and the diversity potential of the community.This research was conducted in Jangkurang Village, Leles District, Garut Regency with the aim of (1) To find out the influence of Religious Scholars Participation on Community Economic Empowerment. (2) The Influence of the Role of the Regional Government on Community Economic Empowerment. (3) The Influence of Religious Scholars Participation and the Role of Regional Governments on Community Economic Empowerment simultaneously. The practical use of the results of this study is expected to be an input for both the government and the community on the position and value of the strategy of the of religious scholars position and regional goverment apparatus in the midst of society.  This research is the explanatory research (explanatory research) of sampling conduction is carried out by a simple random sampling technique model. Collecting data is done by distributing questionnaires to respondents 60 people consisting of businessmen in the village of Jangkurang, Leles distric, Garut from the total population of businessmen in as much as 150 people.The results of this stuy showed that (1) the influence of religious scholars participation gave a positive influence on economic empowerment of Muslim communities in Jangkurang village, Leles district, Garut. (2) The influence of the role of the regional government gave a positive influence on the economic empowerment of Muslim communities in Jangkurang village, Leles district, Garut. And (3) The influence of religious scholars participation and roles of the regional Government gave a positive influence on the economic empowerment of the Muslim community in Jangkurang village, Leles district, Garut.